Altered Gut Microbiota in Children With Hyperuricemia - Xin Yuan; Ruimin Chen; Ying Zhang; Xiangquan Lin; Xiaohong Yang (Frontiers in Endocrinology, 2022)
BackgroundIn adults, gut dysbiosis may contribute to the pathogenesis of gout. However, the characteristics of gut microbiota in children with hyperuricemia (HUA) in the absence of clinical gout have not been explored.ObjectiveThis present study analyzed the gut microbiota in children with HUA as compared to controls (Con) and explored bacterial associations that may account for differences.MethodsA total of 80 children were enrolled in this study; they were divided into HUA and Con according to the level of serum uric acid (UA). The composition of gut microbiota was investigated by 16S rRNA high-throughput sequencing.ResultsPrincipal coordinate analysis revealed that gut microbiota of the HUA group was clustered together and separated partly from the Con group. There was no difference in alpha-diversity between the two groups. However, Spearman’s correlation analysis revealed that serum UA level positively correlated with genera Actinomyces, Morganella, and Streptococcus, and negatively associated with the producers of short-chain fatty acids (SCFAs), such as Alistipes, Faecalibacterium, and Oscillospira, and the sulfidogenic bacteria Bilophila. The members of the genera Alistipes and Bilophila in the Con group were significantly more prevalent than the HUA subjects. Compared to the Con cohort, metabolic pathway predictions found that the superpathways of purine nucleotide de novo biosynthesis were decreased in HUA subjects, whereas the superpathway of purine deoxyribonucleoside de gradation was increased.ConclusionThe composition of the gut microbiota in children with HUA differs from Con. Although causality cannot be established, modification in the microbiota that produces SCFA and sulfide may promote HUA.